Analisis Pengaruh Ukuran Perusahaan, Pertumbuhan Aset, dan Profitabilitas terhadap Struktur Modal Perusahaan Manufaktur Yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021 - Yohanes Remigius; Risal Rinofa; Alfiatul Maulida (Universitas Batanghari, 2022)
This study aims to analyze the effect of firm size, asset growth, and profitability on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 – 2021. The research method used is a quantitative method. The type of data used in this research is secondary data or indirect data. Data sources were obtained from the Indonesian Capital Market Directory (ICMD) for 2019-2021 and through the www.idx.co.id website which lists the company's financial statements. This study uses secondary data in the form of published financial statements of manufacturing companies for 2019 - 2021. The data was obtained from the Indonesia Stock Exchange. In this study, the data analysis used is quantitative analysis, which is a form of data analysis in the form of numbers and by using statistical calculations to analyze hypotheses. The results show that company size has no significant effect on the capital structure of manufacturing companies listed on the IDX in 2019-2021. Asset growth has a significant positive effect on the capital structure of Manufacturing Companies listed on the IDX in 2019-2021. Profitability has a significant positive effect on the capital structure of Manufacturing Companies listed on the IDX in 2019-2021. Company size, asset growth, and profitability simultaneously have a significant effect on the capital structure of Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2019-2021.